2011
DOI: 10.1186/1749-8090-6-57
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of left heart mechanical valve replacement in West African children - A 15-year retrospective study

Abstract: BackgroundThe West African sub-region has poor health infrastructure. Mechanical valve replacement in children from such regions raises important postoperative concerns; among these, valve-related morbidity and complications of lifelong anticoagulation are foremost. Little is known about the long-term outcome of mechanical valve replacement in West Africa. We sought to determine the outcome of mechanical valve replacement of the left heart in children from this sub-region.MethodWe conducted a retrospective rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 19 publications
3
29
0
Order By: Relevance
“…On the other hand two recent reviews from SSA based on their experience both recommended mechanical valves. Edwin et al [6] from Ghana in a 9.1 years follow up of 114 patients undergoing mechanical heart valve replacement with St. Jude and Sorinmonoleaflet valves, observed valve thrombosis in 5 patients, 1 major bleeding, 1 prosthetic valve endocarditis, 2 reoperations and 4 pregnancies without complications. Similarly Williams et al [7] report on 438 South African patients with On-X valve, poorly anticoagulated at follow up of 1.7 years, observed low incidence of hemorrhagic and thrombotic complications and seven full term pregnancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand two recent reviews from SSA based on their experience both recommended mechanical valves. Edwin et al [6] from Ghana in a 9.1 years follow up of 114 patients undergoing mechanical heart valve replacement with St. Jude and Sorinmonoleaflet valves, observed valve thrombosis in 5 patients, 1 major bleeding, 1 prosthetic valve endocarditis, 2 reoperations and 4 pregnancies without complications. Similarly Williams et al [7] report on 438 South African patients with On-X valve, poorly anticoagulated at follow up of 1.7 years, observed low incidence of hemorrhagic and thrombotic complications and seven full term pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…The only patient in our series who had ablation has remained in sinus rhythm for 9 years. While the two reviews on mechanical valves [6] [7] from SSA reported good long and short term results respectively, the health care infrastructures in both Ghana and South Africa are better developed and organized than Nigeria and several other SSA countries, making their results more difficult to reproduce. Another factor likely to favor tissue valve in the horizon is a promising novel low cost stented pericardial valve designed for developing countries like in SSA reported by Legg et al [11] It features a clip in mechanism that secures the valve assembly into the sewing ring stitched independently of the frame and leaflets.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of valve procedure is likely to be informed by a combination of patient, health practitioner choice, demographic and disease factors. A mechanical valve has long term durability providing therapeutic anticoagulation can be achieved compared to a bioprosthetic valve which is likely to degenerate over time [ 1 , 23 , 32 , 33 ]. Mechanical valves may therefore be preferred in younger patients so as to avoid later re-operation.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical intervention remains an important treatment modality for those with more severe forms of RHD, yet disparities exist in access to and outcomes following RHD surgery [ 7 ]. Factors which have been identified as being associated with outcomes following valve surgery in patients with RHD-related valve disease include age [ 8 11 ], pre-operative clinical status [ 8 10 , 12 – 15 ], pre-existing atrial fibrillation (AF) [ 13 , 16 , 17 ], left ventricular function [ 12 – 14 , 18 , 19 ] and the nature of the underlying valve lesion [ 10 , 12 , 13 , 20 ].…”
Section: Introductionmentioning
confidence: 99%